O papel ambiental dos corredores verdes urbanos como elementos integradores da infraestrutura verde - Eckert, Natalia Hauenstein (2016)
The accelerated urbanization process has aggravated the problem of the shortage of urban green areas suitable for the use of the population. The evolution of open spaces in the urban layout configuration was the result of land use process, which began in the Middle Ages. And now in the XXI century suffers from the tendency of leisure facilities that turn to each other, and less for urban living. The resulting way to slow down and minimize the negative effects that this expansion is led to the preservation and qualification of green areas remains. These areas when linear and underused, together form public greenways, which are qualifiers of the urban space. So the study analyzed the climate of existing green corridors in the city of Passo Fundo - RS, as potential components of a network of green infrastructure. Starting as a study, it was listed the air temperature conditions, contact temperature of floors, humidity and amount of natural lighting these green waste city. The case study was conducted in the summer seasons, fall, winter and spring, with analysis of the places with shading from vegetation and in direct sunlight. The results indicated that in shaded places, green corridors are able to minimize the air temperature within 6.6 ° C in summer, and 6.5 ° C in the spring, confirming the positive effect caused by the microclimate these places provide urban atmosphere. Finally, it was part listed one of the routes analyzed for projetual test with recovery measures, restoration and rehabilitation, which serve as guidelines for the others, as a way of acting in the harmonized classification of those public spaces in the urban landscape